Soybean-maize intercropping feasibility under drought-prone area in East Java, Indonesia - Arief Harsono; Dian Adi Anggraeni Elisabeth; Siti Muzaiyanah; SALAM AGUS RIANTO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Harsono A, Elisabeth DAA, Muzaiyanah S, Rianto SA. 2020. Soybean-maize intercropping feasibility under drought-prone area in East Java, Indonesia. Biodiversitas 21: 3744-3754. The study aimed to determine the land productivity, economic feasibility, and soybean cultivar which is suitable for intercropped with maize in maize production center on dryland-upland in East Java, Indonesia. The study was conducted in Semanding and Merakurak Sub-districts, Tuban District, East Java, Indonesia at the end of rainy season (March-July 2019). The study used a factorial randomized block design with three replications. The first factor was planting patterns, namely: soybean intercropping with maize, maize monoculture, and soybean monoculture. The second factor was soybean cultivars, namely: Argomulyo, Dena 1, and Dega 1. The maize variety used was NK Hybrid 212. The result of study indicated that by intercropping and selecting appropriate cultivar, soybean could be developed on dryland-upland area. Soybean intercropping with plant spacing of 30 cm x 15 cm and two seeds per-hill and maize in double row with plant spacing of (40 x 20) cm x 200 cm and one seed per-hill was able to produce maize seeds yield as high as maize increase LER by 1.69, and increase farming income. Dena 1 intercropping with maize was able to provide higher benefit, economic feasibility, and land-use efficiency than Argomulyo and Dega 1, even though Dega 1 had the strongest competitiveness, and Argomulyo had the higher soybean yield.